Seroprevalence of anti-streptolysin O antibodies and its clinical correlates in patients presenting at a tertiary care hospital of southern Haryana: A five year retrospective study - Yadav, Chanchal; Sangwan, Jyoti; Mane, Pratibha; Lohan, Kirti; Yadav, Kumkum; Kumar, Mukesh (Asian Journal of Medical Sciences, 2022)
Background: Streptococcus pyogenes, or group A Streptococcus, in addition to sore throat is responsible for certain non-suppurative diseases, such as acute rheumatic fever and post-streptococcal glomerulonephritis, which occur weeks after the acute infectious process. Anti-streptolysin-O (ASO) titer determination is one of important test sought by clinician. ASO has been shown to vary with age, geographical location, season, and site of infection. Aims and Objectives: To determine the seroprevalence of ASO antibodies and its clinical correlates in a tertiary healthcare facility of Southern Haryana. Materials and Methods: A retrospective cross-sectional study was done on 453 samples received in the Department of Microbiology, Shaheed Hassan Khan Mewati Government Medical College, Nuh, Haryana, on the blood samples received for the detection of ASO, over a period of 5 years (November 2015–October 2020). The data was analyzed for seroprevalence pattern of ASO and association of the same with clinical symptoms. Results: The seroprevalence of ASO antibodies in the present study was found to be 11.3%. Females were more positive than males being 60.8% and 39.2%, respectively. The most common age group involved was 11–20 years. Conclusion: The seroprevalence of ASO antibodies in the present study was found to be 11.3%. Females showed more positivity compared to males. ASO positivity was seen more in the 11–20 years of the age group which could be due to the development of more competent immune system by this age. Arthralgia, fever, carditis, and sore throat were the common clinical presentations. The ASO test is an important investigation being easy to perform even in rural settings providing crucial clue for the diagnosis of post-streptococcal sequelae.